Особливості планування проектів створення кооперативів кормозабезпечення сімейних молочних ферм - Тригуба, Анатолій Миколайович; Боярчук, Анатолій Миколайович; Тригуба, Інна Леонтіївна; Боярчук, Олег Віталійович; Рудинець, Микола Віталійович (НТУ "ХПІ", 2019)
Виконаний аналіз стану молочного тваринництва в Україні. Обґрунтовано потребу реалізації проектів створення кооперативів кормозабезпечення сімейних молочних ферм. Подано особливості планування проектів. Обґрунтовано доцільність врахування мінливих характеристик проектного середовища проектів під час їх планування, що зумовлюють ризик цінності. Означено моделі планування проектів створення кооперативів кормозабезпечення сімейних молочних ферм. Доведено, що ці моделі повинні розроблятися для кожного із етапів їх реалізації, які зумовлюють потребу розгляду різних складових проектів, що є об'єктами планування. Обґрунтовано призначення та головні вимоги до моделей планування проектів із врахуванням ризику. Подано у неявному вигляді залежність цінності продуктів проектів від головних груп чинників проектного середовища. Побудована схема зміни меж ступеня ризику для різних процесів управління проектами впродовж їх життєвого циклу.

The analysis of the condition of dairy cattle breeding in Ukraine is carried out. The necessity of realization of projects’ creation of forage provision cooperatives of family dairy farms is substantiated. The peculiarities of planning of projects for the creation of cooperatives for feed of family dairy farms are presented. The expediency of taking into account the changing characteristics of the project environment of projects for the establishment of cooperatives forage feeding of family dairy farms during their planning, which determine the risk of value, is substantiated. The models of projects’ planning for the creation of cooperatives for the provision of family dairy farms are indicated. It is proved that these models should be developed for each stage of their implementation, which necessitate consideration of various components of projects that are the objects of planning. The purpose and the main requirements for the models of projects’ planning for the creation of forage feeding cooperatives of family dairy farms, taking into account the risk are substantiated. Project’s value dependence on the main groups of their factors is presented. The scheme of changing the risk for different processes of project management of cooperatives creation during their life cycle has been built.
Features of planning projects for the creation of cooperatives forage family dairy farms
Keywords: СМФ; кооператив кормозабезпечення; ризики; життєвий цикл проекту